2018
DOI: 10.1161/jaha.117.007691
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Temporal Trends of Complications Associated With Transvenous Implantable Cardiac Defibrillator Leads

Abstract: BackgroundThe transvenous implantable cardioverter‐defibrillator (ICD) lead is the most common source of complications in a traditional ICD system. This investigation aims to determine the incidence, predictors, and costs associated with these complications using a large insurance database.Methods and ResultsData from the OptumLabs™ Data Warehouse, which include diagnosis, physician and procedure codes, and claims from patient hospitalizations, were analyzed. Patients with a de novo ICD or cardiac resynchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 22 publications
3
45
0
1
Order By: Relevance
“…Notably, our cohort was followed for a considerably longer time, which increases the number of lead‐related complications because leads are the weakest link of the system . The rate of mechanical complications affecting ICD leads after 10 years is approximately 25% . According to a systemic review, the pooled complication rate was 9.1% over a mean follow‐up time of 17.9 months .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our cohort was followed for a considerably longer time, which increases the number of lead‐related complications because leads are the weakest link of the system . The rate of mechanical complications affecting ICD leads after 10 years is approximately 25% . According to a systemic review, the pooled complication rate was 9.1% over a mean follow‐up time of 17.9 months .…”
Section: Discussionmentioning
confidence: 99%
“…Costs began to rise roughly 90 days before the index interval, at which point they peaked, and then declined thereafter to initial levels ( Figure 3 of TV lead complications at 10 years range from 10% to 25%, 7,29,30 implicating TV leads as the component of ICD systems most likely to fail over time. Costs began to rise roughly 90 days before the index interval, at which point they peaked, and then declined thereafter to initial levels ( Figure 3 of TV lead complications at 10 years range from 10% to 25%, 7,29,30 implicating TV leads as the component of ICD systems most likely to fail over time.…”
Section: Costs Of Tv Lead Reoperationmentioning
confidence: 99%
“…Finally, while other studies have included diverse populations of private and publicly insured patients,[7][8][9][10][11] in which the distinction between actual payer costs and provider submitted charges may be less clear and result in inflated cost estimates, we F I G U R E 6 Adjusted length of stay and costs of inpatient lead removal, by the presence of infection. In this study, we observed an increase in complication rates beginning roughly 90 days before TV lead reoperation, and a decrease after reoperation, with a similar pattern in costs.…”
mentioning
confidence: 99%
“…Besides the unequivocal medical benefits, ICD therapy is associated with a risk of complications and increased healthcare costs have been reported . Receiving an ICD is associated with high healthcare costs as the implantation device itself can be as expensive as 30 000 euros .…”
Section: Introductionmentioning
confidence: 99%
“…4 Besides the unequivocal medical benefits, ICD therapy is associated with a risk of complications and increased healthcare costs have been reported. 5 Receiving an ICD is associated with high healthcare costs as the implantation device itself can be as expensive as 30 000 euros. 6 In addition, after implantation, patients are generally followed-up at 1-to-4-month intervals (depending on patients' clinical status and device model) at the outpatient clinic.…”
Section: Introductionmentioning
confidence: 99%